Practical formal synthesis of camptothecin - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Tetrahedron Letter, 2007)
The synthesis of the DE ring of camptothecin using simple and inexpensive starting materials, employing an addition elimination reaction and selective esterification of an aliphatic carboxylic acid as key steps is described. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: alkaloid; Anticancer; camptothecin; Natural product